Türk hukukunda ticari formun korunması - Akoğlu, İbrahim Onur (My University, 2024)
“Türk Hukukunda Ticari Formun Korunması” isimli tez çalışması, Amerika Birleşik Devletleri’nde doğup gelişen ticari form kavramı hakkında Türkiye’de yazılmış eserlerin yalnızca marka veya tasarım düzeyinde kalması, fikri mülkiyet ve haksız rekabet hukuku bağlamında karşılaştırmalı bir incelemeye rastlanmamış olması nedenleriyle, bu alandaki eksikliğin bir nebze olsun giderilmesi amacıyla yazılmıştır. Ticari form en genel haliyle bir ürünün toplam imajı olarak tarif edilmektedir. Ticari form kavramına ilişkin tanımlamadaki zorluklar, koruma çerçevesinin çizilmesinde yaşanan sorunlar ve halihazırda günümüzde yaşanan ölçüsüz genişleme eleştirilerinin yerinde olup olmadığı tezde incelenmiştir. Bu kapsamda tezin ilk bölümünde ticari formun Amerika Birleşik Devletleri ve Avrupa Birliği’ndeki tarihçesi ile Türk Hukukundaki gelişmelerine bakılmış, ikinci bölümde ticari form kavramının fikri mülkiyet ve haksız rekabet hükümleriyle olan ilişkisi ve korumaya ilişkin şartlarına yer verilmiş, üçüncü ve son bölümde ise ticari form niteliği taşıyan ya da taşıyabilecek niteliklere sahip olan örneklere değinilerek Türk Hukukundaki koruma çerçevesi incelenmiştir.

The thesis titled Protection of Trade Dress in Turkish Law is written with the aim of addressing the absence of comparative studies in the context of intellectual property and unfair competition law regarding the concept of trade dress, which originated and developed in the United States. The limitation of existing works in Turkey to the level of trademarks or design only is highlighted, and the thesis aims to partially fill this gap. Trade dress is generally described as the overall image of a product. The difficulties in defining the concept of trade dress the problems encountered in delineating the framework of protection, and the examination of whether the current criticisms of uncontrolled expansion are valid are explored in the thesis. In the context of this thesis, the first section explores the historical development of trade dress in the United States and the European Union, as well as the advancements under Turkish Law. The second section delves into the relationship between the concept of trade dress and intellectual property and unfair competition provisions, while also addressing the conditions for the protection. In the third and final section, the focus shifts to an examination of the framework of protection under Turkish Law by discussing examples possessing or capable of possessing the characteristics of trade dress. This section specifically explores instances within Turkish Law where the protection of trade dress qualities is considered.
Protection of trade dress in Turkish law
Keywords: Copyright; Fikri haklar; fikri mülkiyet; haksız rekabet; Intellectual property; protection of trade dress; Telif hakkı; Ticari form; ticari formun korunması Trade dress; Türkiye; unfair competition